MOBILISASI DINI IBU POST SECTIO CAESAREA DI RSUD SOREANG - Wati Fitri Rahma; Kamsatun Kamsatun (Jurnal Ilmu dan Teknologi Kesehatan, 2018)
ABSTRACTAKI in Indonesia in 2012 is still high at 359 deaths per 100,000 live births. The cause ofmaternal death is bleeding, infection, eclampsi and others. Infection is a complication thatoccurs in many post-sectio caesarea patients due to surgical wounds. This complication canbe prevented by performing physical monitoring and early mobilization actions. The benefitof early mobilization is to accelerate wound healing, with mobilization to facilitate thecirculation of blood. This research is to know the implementation of early mobilization onpost-sectio caesarea patients in RSUD Soreang Kabupaten Bandung 2018. The type ofdescriptive research is quantitative, the population is the mother who gave birth with a sectiocaesarea in RSUD Soreang. Sampling with accidental sampling obtained 31 respondents.The results showed that of 31 post-sectio caesarea mothers as much as 3 people (9.7%)carried out early mobilization so categorized well. While as many as 28 people (90.3%) didnot conduct early mobilization well so categorized not good. It is suggested to health workersto be more intensive in giving motivation and motivation to post SC mothers in earlymobilization.